The Relationship between Career Aspirations, Self-Efficacy, and Subjective Career Success in Sarawak Public Service Department - Ka Ong, Tang; Agatha Lamentan, Muda (UNIMAS Publisher, 2025)
Despite the growing interest in career development within public service sectors, the interactions between career aspirations, self-efficacy, and subjective career success remain underexplored. This descriptive correlational study aimed to examine the relationship between career aspirations, self-efficacy, and subjective career success within the Sarawak Public Service Department. A total of 191 employees, from grade N27 and above, were selected using a non-probability convenience sampling method. The survey instrument was adapted from the Career Aspirations Scale, General Self-Efficacy Scale and Career Satisfaction Scale. The reliability of the scales was confirmed, with Cronbach's alpha values exceeding 0.7 for all variables. The results indicated a significant positive relationship between career aspirations and selfefficacy with subjective career success. Notably, self-efficacy has a dominant influence on subjective career success, surpassing the impact of career aspirations. These findings provide valuable insights into the factors influencing employee motivation and career development within public sector organisations, offering a foundation for enhancing career success strategies.